2009
DOI: 10.1007/s00299-009-0692-4
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of cell-penetrating peptides and delivery of their cargoes in triticale microspores

Abstract: Microspore culture is contributing significantly in the field of plant breeding for crop improvement in general and cereals, in particular. In the present study, we investigated the uptake of fluorescently labeled cell-penetrating peptides (CPP; Tat, Tat(2), M-Tat, peptide vascular endothelial-cadherin, transportan) in the freshly isolated triticale microspores (mid-late uninucleate stage). We demonstrated that Tat (RKKRRQRRR) and Tat(2) (RKKRRQRRRRKKRRQRRR) are able to efficiently transduce GUS enzyme (272 kD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 35 publications
2
45
0
Order By: Relevance
“…The second step involves macropinocytosis for uptake of CPP-cargo complex, and the final step is dependent on parameters such as pH causing disruption of micropinosome resulting in release of the CPP-cargo complex into the cytosol. Our studies on Tat-cargo complex in plant cells do not rule out possibility of simultaneous involvement of various mechanisms for cellular internalization (3,62). This observation is further corroborated by the studies carried by research groups working with mammalian cell lines (64,95).…”
Section: Cellular Internalization Mechanism Of Cpp-driven Cargo Complexsupporting
confidence: 74%
See 2 more Smart Citations
“…The second step involves macropinocytosis for uptake of CPP-cargo complex, and the final step is dependent on parameters such as pH causing disruption of micropinosome resulting in release of the CPP-cargo complex into the cytosol. Our studies on Tat-cargo complex in plant cells do not rule out possibility of simultaneous involvement of various mechanisms for cellular internalization (3,62). This observation is further corroborated by the studies carried by research groups working with mammalian cell lines (64,95).…”
Section: Cellular Internalization Mechanism Of Cpp-driven Cargo Complexsupporting
confidence: 74%
“…Our group has been interest in doubled haploids of man-made cereal triticale because of their applicability in various areas of genetic engineering. Our group is the first one to study CPP-mediated protein transduction and nucleic acid transfection in plant microspores (62). As described in detail later, our results demonstrate notable amenability of microspores toward CPPs and their cargo complex uptake during the transduction and transfection studies.…”
Section: Gametophytic Cellsmentioning
confidence: 56%
See 1 more Smart Citation
“…Despite this progress with mammalian cells, little is known about the ability of GR-MoTrs to enter nonmammalian cells, especially those organisms of research and commercial significance that possess a cell wall. Only a few studies of GR-MoTrs with plant cells have been reported (18)(19)(20)(21)(22) and, to our knowledge, there is only a single investigation of GR-MoTrs with algae (23). In the latter study, Chlorella vulgaris, a species of green algae with a cellulosic cell wall, was found to be impermeable to a GFP-nona-(L)-arginine fusion protein.…”
mentioning
confidence: 93%
“…Transformation efficiency was based on the number of GUSpositive cells. A recent publication on a novel transformation system in triticale involved the use of cell-penetrating peptides (Chugh et al 2009), which have the capability to translocate across cell membranes, and have been used in mammalian systems to move molecules into the cell. It is thought that peptide uptake occurs through pores in the cell membrane.…”
Section: Utilization Of Doubled Haploids In Transformationmentioning
confidence: 99%